Understanding When Teachers Disagree about Student Disability. Issue 2 (3rd April 2018) - Cooc, North
ABSTRACT: The persistent racial and ethnic disparities in special education in the United States raise concerns about the potential misidentification of students. While previous studies have focused on how various student and school factors influence teacher decisions, there is less attention on when teachers disagree about student disability or special education. The current study uses national data from the Educational Longitudinal Study of 2002 to examine when teachers disagreed in their perception of student disability for more than 10, 000 high school students. A unique feature of the data is each student is observed in two different subject classrooms, providing an opportunity to examine how differences in student achievement, behavior, and teacher characteristics influence when teachers disagreed in their judgment of student disability. The results indicate that teachers were more likely to disagree when student behavior varied across classrooms, while differences in student achievement and teacher characteristics were not related to disagreement. The study also found that teachers disagreed more for students who were Black, male, and from lower socioeconomic backgrounds. The main findings highlight how disability is often a context-dependent social construct and have implications for how students are identified for special education.